The Effect of Topical Virgin Coconut Oil on Striae Gravidarum Prevention and Severity: A Randomized Controlled Trial - Ulya, Rahmatul; Sunesni; Yohana Suganda; Mekar Zenni Radhia (HM Publisher, 2024)
Striae gravidarum (SG), commonly known as stretch marks, is a common concern during pregnancy. Virgin coconut oil (VCO) is traditionally used for skin health and may have potential in SG prevention. This randomized controlled trial (RCT) aimed to assess the efficacy of topical VCO in preventing and reducing the severity of SG among pregnant women in Kerinci Regency, Indonesia. Pregnant women (n=200) in their second trimester were randomized to receive either topical VCO or a placebo (standard emollient) twice daily. SG severity was assessed using a modified striae gravidarum assessment scale (SGAS) at baseline, 32 weeks gestation, and six weeks postpartum. VCO application was associated with a significantly lower incidence of new SG compared to the placebo (25% vs. 45%, p < 0.05). Furthermore, the VCO group showed a significant reduction in SG severity at 32 weeks and postpartum (mean SGAS scores: VCO 1.8 vs. placebo 2.6 at 32 weeks, p < 0.05; VCO 1.4 vs. placebo 2.2 at postpartum, p < 0.01). No adverse effects were reported. In conclusion, topical VCO appears to be safe and effective in preventing new SG and reducing the severity of existing SG during pregnancy. Further research is warranted to explore the underlying mechanisms and long-term effects.